(untitled) (Journal of Invasive and Clinical Cardiology, 2025)
Background: Based on epidemiologically research conducted in various countries, it has been found that iron deficiency is prevalent among individuals suffering from heart failure. Objective: The purpose of present study aimed to evaluate the association between Iron deficiency (ID) & severity of chronic Heart Failure(HF) in a tertiary care hospital of Bangladesh. Methods : This analytical cross sectional study conducted at the department of cardiology ,Sir Salimullah Medical College & Mitford hospital for six (6) months-1st July 2021 to 31st December 2021. A total of 96 patients with chronic HF were included & iron profile was evaluated in all the study patients. Severity will be assessed by LVEF(left ventricular ejection fraction) & NYHA(New York heart Association) class. Result : A total of 96 patients were studied with 52.1%were male & 47.9% were female. Mean age of the patients was 58.5±12.3 (SD).years & where the majority were aged 61-70 years. About 54.2 % of patients had ID where 47.9% had absolute ID and 6.3% had functional ID according to the laboratory investigations. Presence of ID was significantly associated with NYHA HF class III & class IV & moderate and severe LV dysfunction (p<0.05).Severity of heart failure according to ejection fraction was also found significantly associated with presence of ID (p<0.001) Conclusion: Study highlight the burden of iron deficiency in HF patients in Bangladesh. Iron deficiency was present in the majority of the patients with chronic heart failure who were evaluated with iron studies. Iron deficiency was also found significantly associated with severity of CHF which leads us to focus on the importance of diagnosing & treating iron deficiency of these patients. J Inv Clin Cardiol 2024; 6(1): 20-24